Antibiotic consumption in India: geographical variations and temporal changes between 2011 and 2019. Issue 5 (26th October 2022) - Fazaludeen Koya, Shaffi; Ganesh, Senthil; Selvaraj, Sakthivel; Wirtz, Veronika J; Galea, Sandro; Rockers, Peter C
Abstract: Objectives: To describe and compare private sector systemic (J01) antibiotic consumption across Indian states from 2011 to 2019. Methods: We used the nationally representative PharmaTrac dataset to describe the consumption rates in DDD across national, state and state-group [high focus (HF) and non-high focus (nHF)] levels. We used median and IQRs to describe and compare across states and state groups, and relative change and compound annual growth rate (CAGR) to examine temporal changes. Results: The annual consumption rate decreased by 3.6% between 2011 and 2019. The share of Access antibiotics decreased (13.1%) and the Access/Watch ratio declined from 0.59 to 0.49. State consumption rates varied widely (HF states reported lower rates) and the inappropriate use increased over the years, especially among HF states. The HF and nHF states showed convergence in the share of the Access and the Access/Watch ratio, while they showed divergence in the use of Discouraged fixed-dose combinations. Conclusions and implications: India's private-sector antibiotic consumption rate was lower than global rates. The rates varied across states and appropriateness of use decreased in most states over the years. States with an increase in appropriate use over time could serve as best practice examples. Studies to understand the factors affecting inappropriate use are required alongside improved data systems to monitor the public-sector provision of antibiotics to understand the total consumption.